The Influence of Physical Work Environment and Work Discipline on Employee Performance in The Kalidoni Village Office - Ade irmawati; Fauziah Afriyani; Try Wulandari (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine how the influence of the physical work environment and work discipline on employee performance at the kalidoni village office. In this study collected through distributing questionnaires with 57 respondents. The theory used in this study relates to the physical work environment and work discipline. This type of research uses research instruments in the form of questionnaires and data analysis techniques using IBM SPSS V25 for windows. There are also data analysis techniques in this study including multiple linear analysis validity tests, t tests, f tests and determination tests. From the results of the tests carried out partially the physical work environment has a significant positive effect on employee performance of 0.00 and work discipline has a positive and significant effect on employee performance of 0.023 and simultaneously the physical work environment and work discipline on employee performance have a positive and significant effect on employee performance of 0.00.